1997
DOI: 10.1080/00039899709602221
|View full text |Cite
|
Sign up to set email alerts
|

Induced Production of Nitric Oxide, Tumor Necrosis Factor, and Interleukin-6 in RAW 264.7 Macrophages by Streptomycetes from Indoor Air of Moldy Houses

Abstract: Dampness and mold growth in buildings cause spore generation into indoor air, which is associated with respiratory tract disorders. Specific agents or cellular mechanisms of diseases have not yet been identified. In this study, airborne spores of Streptomyces sp., isolated from moldy houses, stimulated RAW264.7 macrophages, which produced tumor necrosis factor alpha and interleukin-6 and induced the expression of inducible nitric oxide synthase, with subsequent nitric oxide production. Spores of other microorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
20
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 28 publications
6
20
0
Order By: Relevance
“…These results corroborated our in vitro findings, which demonstrated that the spores of streptomycetes effectively induced mouse RAW264.7 macrophages to produce proinflammatory mediators (TNF-␣, IL-6, IL-1, and NO) (10)(11)(12). Individuals in moisture-damaged buildings usually experience repeated exposures to relatively low doses of the spores, and thus, it seemed of interest to study the responses caused by repeated exposures to the spores over a wide dose range in vivo.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…These results corroborated our in vitro findings, which demonstrated that the spores of streptomycetes effectively induced mouse RAW264.7 macrophages to produce proinflammatory mediators (TNF-␣, IL-6, IL-1, and NO) (10)(11)(12). Individuals in moisture-damaged buildings usually experience repeated exposures to relatively low doses of the spores, and thus, it seemed of interest to study the responses caused by repeated exposures to the spores over a wide dose range in vivo.…”
supporting
confidence: 77%
“…The strain, encoded strain A4 in our previous in vitro studies (10)(11)(12), was identified by the Deutsche Sammlung von Mikroorganismen und Zellkulturen (Braunschweig, Germany) identification service. The microbe was cultured on Tryptone yeast-glucose agar (Bacto Plate Count Agar; Difco Laboratories, Detroit, Mich.) and incubated at 20°C in the dark for about 5 days.…”
Section: Materials and Methods Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…NO in the supernatant was assayed by the Griess reaction as the stable NO oxidation product nitrite [14], as described earlier [15]. Expression of iNOS in the cells of NAL was determined with Western blot analysis [15] with minor modifications.…”
Section: Nitric Oxide Analysismentioning
confidence: 99%
“…Expression of iNOS in the cells of NAL was determined with Western blot analysis [15] with minor modifications.…”
Section: Nitric Oxide Analysismentioning
confidence: 99%